Crown–rump length discordance and adverse perinatal outcome in twin pregnancies: systematic review and meta‐analysis. (August 2014) - D'Antonio, F.; Khalil, A.; Pagani, G.; Papageorghiou, A. T.; Bhide, A.; Thilaganathan, B.
ABSTRACT Objective The aim of this systematic review was to explore the relationship between crown–rump length (CRL) discordance detected at 11–14 weeks of gestation and adverse outcome in twin pregnancy and to assess its predictive accuracy. Methods A protocol designed a priori following MOOSE guidelines and recommended for systematic review and meta‐analysis was used. The outcomes observed were: total fetal and perinatal loss, fetal loss at < 24 weeks, fetal loss at ≥ 24 weeks, birth‐weight (BW) discordance, preterm delivery (PTD) at < 34 weeks and fetal anomalies. The analysis was performed for all twins and for dichorionic (DC) and monochorionic (MC) twins separately. Results A total of 2008 articles were identified and 17 studies were included in the systematic review. Twin pregnancies with CRL discordance ≥ 10% were at significantly higher risk of perinatal loss (RR, 2.80; 95% CI, 1.25−6.27; P = 0.012), fetal loss at ≥ 24 weeks (RR, 4.07; 95% CI, 1.47−11.23; P = 0.006), BW discordance (RR, 2.24; 95% CI, 1.89–2.64; P < 0.001) and PTD at < 34 weeks (RR, 1.49; 95% CI, 1.23−1.80; P < 0.001) but not of fetal loss at < 24 weeks (P = 0.130). A meta‐analysis of fetal anomalies was not possible because fewer than two studies explored this outcome. However, when used alone to screen for adverse pregnancy outcome, the predictive accuracy of CRL discordance was low for each of the outcomes explored. Conclusion CRL discordance is associated with an increased risk of adverse pregnancy outcome. However, the accuracy of CRL discordance in predicting adverse outcome is poor and thus limits its routine use in clinical practice. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd